2019
DOI: 10.1002/ejlt.201800472
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Olive Leaf Yellowing Associated Virus on Olive (Olea europaea L.) Oil

Abstract: Among the 15 virus species detected in olive trees, Olive leaf yellowing associated virus (OLYaV) is found with high incidence and frequency in Southern Italy in particular. Effects of OLYaV on virgin olive oil yield and quality of Leccino and Ottobratica cultivars in the Calabria region (Southern Italy) are analyzed. Oil yield, free acidity, number of peroxides, spectrophotometric indices, total content of chlorophylls and carotenoids, total phenol content, composition of the fatty acids, total tocopherols, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The phytosanitary analyses showed that Apulian olive germplasm is in overall good phytosanitary status. OLYaV was the predominant viral agent, in accordance with the past evidences in Southern Italy (Fontana et al, 2019), while only seven genotypes were infected by CLRV. The sanitation treatments adopted resulted very effective in eliminating both viruses with 83% and 92% efficiency for in vivo and in vitro thermotherapy, respectively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The phytosanitary analyses showed that Apulian olive germplasm is in overall good phytosanitary status. OLYaV was the predominant viral agent, in accordance with the past evidences in Southern Italy (Fontana et al, 2019), while only seven genotypes were infected by CLRV. The sanitation treatments adopted resulted very effective in eliminating both viruses with 83% and 92% efficiency for in vivo and in vitro thermotherapy, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…An essential prerequisite in the genetic resources' conservation is also the assessment of the phytosanitary status (Fontana et al, 2019). As for other vegetative propagated crops, olive is affected by several pathogens (viruses, fungi, bacteria and phytoplasmas) that persist in the budwood and can be transmitted and disseminated with it, with severe economic effects on yield and production quality (Martelli et al, 2002;Loconsole et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Only a small quantity of the total phenols was transferred from drupes to the oils: EVO in fact possessed 0.03–1.15 g GA kg −1 , with higher results generally in the first production period. EVO of Ottobratica cv extracted in October were the samples with the highest TPC (1.15 g GA kg −1 ) among studied samples and with respect to other observations for the same cultivar and similar extraction processing 26–28 . Despite the varietal differences, this parameter can indeed vary among crop years, linked to the plant response toward environmental conditions 29,30 .…”
Section: Resultsmentioning
confidence: 51%
“…A decrease in oil yield and maturity index in virus infected olives was also reported, as well as elevated total phenols in olive oil content from infected olives when compared to healthy fruits (Godena et al, 2012). Nevertheless, the Olive leaf yellowing associated virus (OLYaV) was not found to have a negative interference in oil yield and quality (Fontana et al, 2019).…”
Section: Introductionmentioning
confidence: 99%